2016
DOI: 10.1186/s12943-016-0492-8
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of cryptochrome genes in human colorectal cancer

Abstract: BackgroundCircadian disruption and deranged molecular clockworks are involved in carcinogenesis. The cryptochrome genes (CRY1 and CRY2) encode circadian proteins important for the functioning of biological oscillators. Their expression in human colorectal cancer (CRC) and in colon cancer cell lines has not been evaluated so far.MethodsWe investigated CRY1 and CRY2 expression in fifty CRCs and in the CaCo2, HCT116, HT29, SW480 cell lines.ResultsCRY1 (p = 0.01) and CRY2 (p < 0.0001) expression was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Cell number and density of viable cells were determined using CAsy Cell Counter (Innovatis, Sittingbourne, UK) as previously reported [57]. Briefly, each sample (cell suspension) was prepared three times in CAsyTon (Innovatis) buffer, followed by triplicate measurements of 200 μl sample volume.…”
Section: Methodsmentioning
confidence: 99%
“…Cell number and density of viable cells were determined using CAsy Cell Counter (Innovatis, Sittingbourne, UK) as previously reported [57]. Briefly, each sample (cell suspension) was prepared three times in CAsyTon (Innovatis) buffer, followed by triplicate measurements of 200 μl sample volume.…”
Section: Methodsmentioning
confidence: 99%
“…This trend was generally preserved in sub-groups of patients, but the difference reached level of significance only in left-sided colorectum in men. There is a substantial data supporting the assumption that expression of cry2 in colorectal tumor tissue differs in comparison to adjacent healthy mucosa [17,18]. Expression of cry2 was down-regulated in colorectal tissue, similar to other genes involved in the circadian feedback loop (i.e., per1 and per2) [17,18].…”
Section: Figure 2 Five-year Survival Curves For Women Patients With mentioning
confidence: 67%
“…Recent knowledge of CRC induced changes in cry1 expression is inconclusive [17][18][19]. It is possible that changes in cry1 expression may be linked to certain clinical and pathological features because reduced levels of cry1 expression were observed in females, older patients (62-74 years) and in tumors located in the transverse colon [18]. Another study reports the highest expression of cry1 in tumors located in the distal colon compared to other colon parts [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased mRNA or protein expressions of Cry1 and/or Cry2 were reported for human HCC, as well as for human cancers of the breast, endometrium, ovary, prostate, colon, pancreas, head-and-neck, brain, skin and blood cells. [39][40][41][42] Yet, the relevance of Cry1/Cry2 deficiency for carcinogenesis was debated. A prior report showed that Cry1/Cry2 deficiency promoted g-radiation-induced lymphomas in mice.…”
Section: Discussionmentioning
confidence: 99%